Tailored intervention improves statin adherence and reduces LDL-cholesterol levels - Wenny Putri Nilamsari; Novika Selvia Putri; Mochamad Yusuf Alsagaff; Halim Priyahau Jaya; Budi Suprapti; Neni Tri Astuti; Hikmah Urwatil Wusqo (Pharmacia)
Background: Inadequate compliance with statin therapy considerably affects the achievement of low-density lipoprotein cholesterol (LDL-C) objectives. Tailored interventions aim to address individual patient barriers to improve medication adherence. Objective: The objective of this study was to assess the efficacy of a tailored intervention in improving statin adherence and reducing LDL-C levels in patients with atherosclerotic cardiovascular disease (ASCVD). Methods: A prospective one-group study utilizing a pre-test and post-test design was conducted, involving 70 patients. The inclusion criteria were: 1) patients with baseline LDL-C values recorded prior to the intervention; 2) patients who had undergone 40 mg atorvastatin therapy for a minimum of three months without reaching LDL-C targets; and 3) non-adherent patients. Adherence was assessed using the Short Form of the Adherence to Refills and Medications Scale (ARMS-SF) questionnaire. Results: After the intervention, adherence improved significantly from 0% to 90% (p < 0.001), accompanied by a significant reduction in mean LDL-C levels from 100.19 mg/dL to 87.29 mg/dL (p < 0.001). Conclusion: Tailored intervention significantly improved adherence and reduced LDL-C levels. This method can be recommended as an effective strategy to improve medication adherence prior to therapy intensification or polymorphism testing in patients on high-intensity statin therapy.